Compliance, illiteracy and low-protein diet: multiple challenges in CKD and a case of self-empowerment. Issue 1 (December 2016) - Maxia, Stefania; Loi, Valentina; Capizzi, Irene; Piccoli, Giorgina; Cabiddu, Gianfranca; Pani, Antonello
Abstract Background Low-protein diets (LPD) are an important means of delaying the need for dialysis and attaining a stable metabolic balance in chronic kidney disease (CKD). Many authors consider a low educational level and illiteracy to be adverse features for a good dietary compliance. Case presentation We report the case of a 77-year old woman, illiterate, affected by advanced CKD (stage 4 according to KDIGO guidelines). She was initially ashamed of her problem and did not declare it, leading to an overzealous reduction in protein intake. However, with her daughter's help, who translated the dietary prescription into images, she overcame the barrier represented by illiteracy and was able to correctly follow the prescriptions, attaining good kidney function stability and preserving an adequate nutritional status. Conclusions The case underlines the importance of a personalized approach to dietary prescriptions and suggests that it is possible to achieve a good compliance to the dietary treatment of CKD also in patients with relevant cultural barriers.